Mekanisme Penyelesaian Sengketa Pinjam Meminjam Uang Berbasis Teknologi Informasi (Fintech Lending) Menurut Ketentuan Peraturan Perundang-Undangan di Indonesia - Ilka Sandela; Nila Trisna; Adam Sani (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Technological developments cause various developments in people's lives, one of which is in terms of lending and borrowing money. Currently, information technology-based lending and borrowing services are available based on agreements. In its implementation, it is possible for the parties not to carry out things in accordance with the agreement, causing a dispute. The purpose of this research is to study further in relation to the regulation of information technology-based lending and borrowing dispute settlements based on the provisions of laws and regulations in Indonesia and how the dispute resolution mechanism is. The research method used is the normative juridical method. The results of the study show that the regulation of technology-based lending and borrowing dispute resolution is not regulated in detail in the specific regulations, namely the Financial Services Authority Regulation Number 77/PJOK.01/2016 concerning Technology-Based Money-Lending and Borrowing Services and Bank Indonesia Regulation No.19/12/ PBI/2017 concerning the Implementation of Financial Technology. So, to determine what dispute resolution mechanisms can be done, it can refer to the legal umbrella for electronic transactions, namely Law Number 11 of 2008 concerning Information and Electronic Transactions as amended by Law Number 19 of 2016 (UU ITE). According to the Information and Electronic Transactions Law, electronic transaction dispute resolution mechanisms can be resolved through civil lawsuits, arbitration and other dispute resolution institutions.